The Relationship Between Duration Disease and Glucose Blood Related to Subjective Compliance in Diabetes Mellitus - Nur Lailatul Lathifah (Jurnal Berkala Epidemiologi, 2017)
Diabetes mellitus (DM) is often called the silent killer because this disease can affect all organs of the body and cause several kinds of complaints. Tambaksari Sub-district, Surabaya City in 2013 had a high DM case and was still a health problem because it had a DM prevalence rate exceeding the East Java prevalence rate of 2.1% and was greater than the DM prevalence rate in Indonesia which was 1.5%. The purpose of this study was to analyze the duration of the disease and blood sugar levels with subjective complaints in people with DM type 2 at the Public health center (PHC) of Rangkah and Pacarkeling. This type of research uses observational analytic with a cross-sectional method. The samples in this study were 50 DM type 2 patients. The sampling technique uses simple random sampling, researchers conducted interviews with the help of questionnaire instruments. The dependent variable in this study is subjective complaints, while the independent variable is the duration of the disease and blood sugar levels. Data analysis using the Chi-Square test. The results of the study indicate that there is a relationship between the duration of the disease with subjective complaints in patients with DM type 2 (p = 0.049) and blood sugar levels with subjective complaints in patients with DM type 2 (p = 0.004). Based on this analysis it can be concluded that there is a relationship between the duration of the disease and blood sugar levels with subjective complaints in patients with DM type 2. Suggestions research is to the health center in order to increase knowledge and information to patients with DM type 2 about the dangers of diabetes mellitus in the form of complications and how to handle it.